Pencarian Resep Makanan Berdasarkan Citra Makanan Menggunakan Simple Morphological Shape Descriptors, Cie L*A*B* Color Moment Dan Local Binary Pattern - Yosua Dwi Amerta; Yuita Arum Sari; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
A recipe is a guide that contains the ingredients, steps, and how to serve a food. Recipe searches are generally limited to using the title or name of a food, and to overcome these limitations image search is needed. Image based search requires extraction of image features, and there will be 3 feature extraction methods to be used. Extracting color features is done using the CIE L * a * b * Color Moment method, which will take the features of the mean, standard deviation, and skewness. In the shape feature, Simple Morphological Shape Descriptors (SMSD) is used to get 4 feature, aspect ratio, length, width, and diameter features. The third feature, which is texture extracted using the Local Binary Pattern method. Based on the results of these methods, it can be seen that the search uses CIE L * a * b * Color Moment gets the MAP value of 0.70. The SMSD method gets the smallest MAP with a value of 0.46. LBP gets the same value with the combined method which is 0.52. So it can be concluded that LBP has major effects to the results of the combined method.